Determination of iron and aluminum based on the catalytic effect on the reaction of xylene cyanol FF with hydrogen peroxide and potassium periodate - Cai,Longfei (2011)
A simple, sensitive and selective method for the simultaneous determination of trace iron and aluminum by catalytic spectrophotometry is presented. This method is based on the catalytic effects of iron and aluminum on the reaction of xylene cyanol FF with hydrogen peroxide and potassium periodate. Both iron and aluminum did not show catalytic effects on the oxidation reaction of xylene cyanol FF in the presence of either hydrogen peroxide or potassium periodate. However, significant catalytic effects of iron and aluminum were obtained when the two oxidants were simultaneously used. Linear calibration graphs were obtained from 3.57 × 10-8 to 3.57 × 10-7 mol L-1 for Fe and from 1.48 × 10-7 to 1.48 × 10-6 mol L-1 for Al. The detection limits, based on the 3-fold standard deviation criterion, were 1.50 × 10-8 mol L-1 for Fe and 6.10 × 10-8 mol L-1 for Al. This method was applied to the simultaneous determination of trace iron and aluminum in tap water, lake water, river water and tea leaves without separation and preconcentration. Contents of Fe and Al in tap water, lake water and river water were 3.13 × 10-7, 3.21 × 10-7, 2.74 × 10-7 mol L-1 for Fe and 1.31 × 10-6, 9.83 ×10-7, 1.43× 10-6 mol L-1 for Al, respectively. Tea leaves contained 3.10 × 10² µg g-1 Fe and 7.37 × 10² µg g-1 Al. Further research is required for understanding the catalytic mechanism of iron and aluminum on this novel oxidation reaction.